NPT100-18A rescues mitochondrial oxidative stress and neuronal degeneration in human iPSC-based Parkinson's model. - Alecu, Julian; Sigutova, Veronika; Brazdis, Razvan Marius; Lörentz, Sandra; Marios-Evangelos, Bogiongko; Nursaitova, Anara; Regensburger, Martin; Roybon, Laurent; Galler, Kerstin Martina; Wrasidlo, Wolfgang; Winner, Beate; Prots, Iryna (BMC Neuroscience, 2025)
BACKGROUND: Parkinson's disease (PD) is a neurodegenerative disorder characterized by protein aggregates mostly consisting of misfolded alpha-synuclein (αSyn). Progressive degeneration of midbrain dopaminergic neurons (mDANs) and nigrostriatal projections results in severe motor symptoms. While the preferential loss of mDANs has not been fully understood yet, the cell type-specific vulnerability has been linked to a unique intracellular milieu, influenced by dopamine metabolism, high demand for mitochondrial activity, and increased level of oxidative stress (OS). These factors have been shown to adversely impact αSyn aggregation. Reciprocally, αSyn aggregates, in particular oligomers, can impair mitochondrial functions and exacerbate OS. Recent drug-discovery studies have identified a series of small molecules, including NPT100-18A, which reduce αSyn oligomerization by preventing misfolding and dimerization. NPT100-18A and structurally similar compounds (such as NPT200-11/UCB0599, currently being assessed in clinical studies) point towards a promising new approach for disease-modification. METHODS: Induced pluripotent stem cell (iPSC)-derived mDANs from PD patients with a monoallelic SNCA locus duplication and unaffected controls were treated with NPT100-18A. αSyn aggregation was evaluated biochemically and reactive oxygen species (ROS) levels were assessed in living mDANs using fluorescent dyes. Adenosine triphosphate (ATP) levels were measured using a luminescence-based assay, and neuronal cell death was evaluated by immunocytochemistry. RESULTS: Compared to controls, patient-derived mDANs exhibited higher cytoplasmic and mitochondrial ROS probe levels, reduced ATP-related signals, and increased activation of caspase-3, reflecting early neuronal cell death. NPT100-18A-treatment rescued cleaved caspase-3 levels to control levels and, importantly, attenuated mitochondrial oxidative stress probe levels in a compartment-specific manner and, at higher concentrations, increased ATP signals. CONCLUSIONS: Our findings demonstrate that NPT100-18A limits neuronal degeneration in a human in vitro model of PD. In addition, we provide first mechanistic insights into how a compartment-specific antioxidant effect in mitochondria might contribute to the neuroprotective effects of NPT100-18A.
EVALuna2:586322
Keywords: iPSC; Dopaminergic neurons; Alpha-synuclein; Aggregation; Parkinson’s disease; Oxidative stress; NPT100-18A; Mitochondria; ROS